STANDARDISATION AND QUALITY EVALUATION OF FRUIT PULP BASED YOGHURTS - LOVELY MARIYA JOHNY, SEEJA THOMACHAN PANJIKKARAN*, E. R. ANEENA, C.L. SHARON and P.S. LAKSHMY, (The Journal of Research ANGRAU, 2021)
Nutritious and palatable yoghurts with diversified flavours were prepared by adding sapota andguava fruit pulps. Incorporation of 10-20% fruit pulp has imparted acceptable organoleptic qualitiesto yoghurts, with the moisture, pH and total acidity levels unaltered. During fortnight storage, thewater holding capacity of sapota pulp-based yoghurt has only slightly changed from 50.46% to 53.00%whereas, it was 50.34% to 52.80% in guava pulp-based yoghurt. Syneresis initiated on the tenth dayof storage was at 0.5% and 1.0% level in the fruit pulp-based yoghurts and plain yoghurt, respectively,which increased to 0.6% and 1.02% on fifteenth day. Energy and fat contents were higher in plainyoghurt. Fruit yoghurts were found to have higher amounts of â carotene, vitamin C, iron and potassiumcompared to the plain yoghurt. Thus, the enrichment with sapota and guava pulps made the yoghurtshealthier and opened the possibility for product diversification.